Bipolar plasma vaporization using plasma-cutting and plasma-loop electrodes versus cold-knife transurethral incision for the treatment of posterior urethral stricture: a prospective, randomized study - Wansong Cai; Zhiyuan Chen; Liping Wen; Xiangxin Jiang; Xiuheng Liu (Clinics, 2016)
OBJECTIVE: Evaluate the efficiency and safety of bipolar plasma vaporization using plasma-cutting and plasma-loop electrodes for the treatment of posterior urethral stricture. Compare the outcomes following bipolar plasma vaporization with conventional cold-knife urethrotomy. METHODS: A randomized trial was performed to compare patient outcomes from the bipolar and cold-knife groups. All patients were assessed at 6 and 12 months postoperatively via urethrography and uroflowmetry. At the end of the first postoperative year, ureteroscopy was performed to evaluate the efficacy of the procedure. The mean follow-up time was 13.9 months (range: 12 to 21 months). If re-stenosis was not identified by both urethrography and ureteroscopy, the procedure was considered “successful”. RESULTS: Fifty-three male patients with posterior urethral strictures were selected and randomly divided into two groups: bipolar group (n=27) or cold-knife group (n=26). Patients in the bipolar group experienced a shorter operative time compared to the cold-knife group (23.45±7.64 hours vs 33.45±5.45 hours, respectively). The 12-month postoperative Qmax was faster in the bipolar group than in the cold-knife group (15.54±2.78 ml/sec vs 18.25±2.12 ml/sec, respectively). In the bipolar group, the recurrence-free rate was 81.5% at a mean follow-up time of 13.9 months. In the cold-knife group, the recurrence-free rate was 53.8%. CONCLUSIONS: The application of bipolar plasma-cutting and plasma-loop electrodes for the management of urethral stricture disease is a safe and reliable method that minimizes the morbidity of urethral stricture resection. The advantages include a lower recurrence rate and shorter operative time compared to the cold-knife technique.